(untitled) (Polish Yearbook of International Law, 2021)
The article offers a revisited look at the classic jurisprudence of the ECtHR and CJEU concerning the Turkish Republic of Northern Cyprus from the perspective of the phenomenon of judicial dialogue. In this context, it aims to examine whether judicial dialogue contributes to the development of coherent jurisprudence and in consequence of effective judicial redress in cases involving unrecognised entities and individuals. It draws attention to the threats for both the international rule of law and the protection of rights of individuals resulting from inconsistencies within own jurisprudence of the respective court, as well as from lack of coherence in interpretation and application of the same rules of international law by different courts.